2016
DOI: 10.1177/1934578x1601100901
|View full text |Cite
|
Sign up to set email alerts
|

A Computational Examination of the Uncatalyzed Meinwald Rearrangement of Monoterpene Epoxides

Abstract: Epoxides are relatively reactive compounds and may undergo decomposition or rearrangement reactions at elevated temperatures, and gas chromatographic analysis of essential oils may cause thermal decomposition or rearrangement of epoxide components at gas chromatographic temperatures. Density functional theory (DFT) calculations were carried out using the B3LYP functional at the 6-311++G**//6-31G* level of theory on the Meinwald rearrangements of αpinene oxide (two different mechanisms leading to trans-pinocamp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Such large difference is in agreement with the observed reactivity trend, with the aromatic epoxides reacting smoothly (Scheme ) and the aliphatic ones requiring a Lewis acid cocatalyst to give reasonable conversions (see Table S1 in the Supporting Information and Scheme ). To investigate the role of Lewis acids, we computed the BF 3 -cocatalyzed ring opening of aliphatic epoxide 2l′ (Scheme ). It was found that BF 3 -mediated reactions have lower barriers than those without BF 3 (Scheme ) by 15.3 and 11.3 kcal/mol for the formation of primary and secondary alcohols, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Such large difference is in agreement with the observed reactivity trend, with the aromatic epoxides reacting smoothly (Scheme ) and the aliphatic ones requiring a Lewis acid cocatalyst to give reasonable conversions (see Table S1 in the Supporting Information and Scheme ). To investigate the role of Lewis acids, we computed the BF 3 -cocatalyzed ring opening of aliphatic epoxide 2l′ (Scheme ). It was found that BF 3 -mediated reactions have lower barriers than those without BF 3 (Scheme ) by 15.3 and 11.3 kcal/mol for the formation of primary and secondary alcohols, respectively.…”
Section: Resultsmentioning
confidence: 99%